Aligning Teaching Philosophy Statements with Practice: An Evidence-Based Approach Using Retrospective Think-Aloud Protocols - John Blake (MDPI AG, 2024)
Teaching philosophy statements are often declarations of beliefs interspersed with descriptions and metaphors. The disjuncture between the stated philosophy and actual teaching has been raised by numerous academics. This case study addresses the neglected area of grounding teaching philosophies on actual teacher behaviour rather than on espoused beliefs. This study includes a replicable framework for teachers to create evidence-based teaching philosophy statements through a systematic investigation of their actual teaching practices. A retrospective think-aloud protocol was used to recount a lesson. Using a transcript of the recount, the teacher's actions were identified, extracted, and justified following pre-determined protocols. References to theoretical and empirical studies supporting or contradicting the justifications were checked in the research literature. To counteract potential self-bias, colleagues' views on the reasons selected were surveyed. The discrepancy between the teacher's justification of actions and the peers' perspectives revealed hitherto hidden idiosyncrasies and underlying values.